UiTM health festival 2025: bijak di pinggan, sihat di badan - Mohamed Yusoff, Mohamad Zuhair; Ahmad Nazari, Mohamad Asraf; Yaacob, Siti Sara; Muzaini, Kamarulzaman; Mohamad, Mariam; Suddin, Leny Suzana; Xin Wee, Chen (Faculty of Medicine, 2025)
The health promotion programme, held on 23 August 2025 at Masjid Al-Ehsan, Seksyen 24, was organised by Year 4 medical students (Group 4) under the supervision of Assoc. Prof. Dr. Siti Sara Yaacob and Dr. Kamarulzaman Muzaini, in collaboration with Majlis Bandaraya Shah Alam. It featured health screenings, hands- on education stations translating guidelines into daily choices, and mental health awareness. Residents learned about label reading, calorie awareness, the “tiga serangkai” prevention, obesity and malnutrition, and the risks of smoking and vaping, supported by a bilingual take-home booklet. The programme aimed to turn health advice into action, encouraging wise daily choices to protect long-term health.The Health Promotion Programme received strong support and guidance, featuring key guests including Tuan Haji Ahmad Dahlan Kardi, Nazir of Masjid Al Ehsan Seksyen 24, and Assoc. Prof. Dr. Leny Suzana Suddin, Deputy Dean of ICAN. The programme was officially opened by Puan Siti Nur Aishah Mohd Zain from Majlis Perwakilan Penduduk MBSA Zon 8.